On the Equivalence Between Logic Programs and Bipolar Argumentation Frameworks - Cordeiro, Renan; Alcântara, João (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2024)
In this paper, we extend the connection between argumentation formalisms and logic programs, by showing the equivalence between bipolar argumentation β-semantics and various 3-valued logic programming semantics. In particular, we show that β-semi-stable semantics corresponds to L-stable semantics, which has been previously shown not to be expressible by traditional attack-only argumentation frameworks. Besides enhancing our understanding of how logic programs relate to argumentation with support, we provide direct translations between them and their semantics, allowing their interchangeable use.